A review on the variable copies of C-C motif chemokine ligand 3 like 1 (CCL3L1) gene among different populations and current methods for quantification - Jamaluddin, Jalilah; Abu Bakar @ Jamaludin, Suhaili (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
C-C motif Chemokine Ligand 3 Like 1 (CCL3L1) is characterized as a gene with copy number variable (CNV) and clustered at the segmental duplication on chromosome 17q12. CCL3L1 is responsible for the production of macrophage inflammatory protein (MIP) 1α that plays an important function in the immune system and host defense. Various copies range of CCL3L1 have been reported and associated with the diseases in different populations. Thus, this review aimed to summarise the distribution of CCL3L1 copy number from different populations according to the geographical region and highlighted the lacking of data from Malaysian population, which is one of the multi-ethnic countries due to the impacts of CCL3L1 copies on various diseases. Besides, we also outlined the methodologies available for the copy number typing. In overall, this review could provide significant information on the role of CCL3L1 copies in disease association and as well as providing evidence on the population diversity.